The influence of the local government on Serbia's economic development and its debt reduction - Aničić Jugoslav; Aničić Dušan; Jelić Miloje A.; Gligorijević Jasmina (Trendovi u Poslovanju)
Transitional processes since the year 2000 have additionally potentiated and multiplied the negative effects of the economic policy. The models of the economic growth and development have been based upon sector priorities and policies, mainly short-term and medium-term objectives, without a clear long-term development strategy. It resulted in a low gross domestic product, high rate of unemployment, and high public debt. Most of the local governments have had a negligible role in the conduct of the economic policy, but the negative effects of the macroeconomic policy remained a burden for them. The local governments mainly conducted the economic policy development on their own because the development policy has not been conducted at the regional level, as in many developed countries. Modern times ask for a proactive approach on behalf of the local governments concerning the economic development, more influence on the republic authorities and entrepreneurial spirit development in business, with the aim of unemployment and public debt reduction.